Fourier transform infrared spectroscopy-Partial Least Squares (FTIR-PLS) coupled procedure application for the evaluation of fly attack on olive oil quality - Gómez Caravaca, Ana María (2013)
A Fourier transform infrared spectroscopy–Partial Least Squares (FTIR–PLS) strategy for the determination of the quality of olive fruits and the respective virgin olive oil (VOO) has been developed. This methodology has been demonstrated as able to correlate the level of fly attack in olive oils with their FTIR spectra. A multivariate calibration model was built by the PLS algorithm using the 4000–700 cm−1 spectral range on pretreated data and an evaluation of some of the usual quality parameters of VOO (free acidity, fatty acids composition, oxidative stability by OSI time and phenolic compounds obtained by capillary electrophoresis) and was performed to corroborate the real influence of fly attack on the quality of the oils. Furthermore, the evaluation of the FTIR data showed some differences in the regions of the fatty acids and phenolic compounds depending on the percentage of fly attack on the olives. This non-destructive method easily allows a non-destructive measure and, at the same time, establishes the level of Bactrocera oleae attack in olive fruit thus analysing directly the olive oil obtained without any previous treatment.